Can Parental Migration Reduce Petty Corruption in Education? - Hockel, Lisa Sofie (World Bank, Washington, DC, 2017)
The income generated from parental migration can increase funds available for children's education. In countries where informal payments to teachers are common migration could therefore increase petty corruption in education. This hypothesis is tested by investigating the effect of migration on educational inputs. An instrumental variables approach is used on survey data and matched administrative records from the World Bank's Open Budget Initiative (BOOST) from Moldova, one of the countries with the highest emigration rates. Contrary to the positive income effect, the strongest migration-related response in private education expenditure that is found is a substantial decrease in informal payments to public school teachers. Any positive income effect due to migration must hence be overcompensated by some payment-reducing effects. A number of potential explanations at the family level, school level or community level are discussed, several of these explanations ruled out and possible interpretations for future research highlighted.